Polymorphisms of IL23R and Fuchs’ syndrome in a Chinese Han population - Zhou, Hongyan (Molecular Vision, 2010)
PURPOSE: The aim of the study was to investigate the association of polymorphisms of the interleukin-23 receptor (IL23R) gene with Fuchs’ syndrome in a Chinese Han population. METHODS: Three single-nucleotide polymorphisms (SNPs), rs7517847, rs11209032 and rs17375018 of IL23R were genotyped in 138 Chinese Han patients with Fuchs’ syndrome and 407 healthy controls by using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Data were analyzed by χ(2) analysis. RESULTS: All genotype and allele distributions in patients with Fuchs’ syndrome and healthy controls were in Hardy–Weinberg equilibrium. The frequency of the rs11209032 AA genotype was significantly increased in patients with Fuchs’ syndrome as compared to controls (corrected p [pc]=0.036, OR 1.86, 95%CI 1.21 to 2.86). There were no statistically significant differences between patients and healthy controls concerning the other two tested SNPs (rs17375018 and rs7517847). The haplotypes of the tested SNPs were not different between patients and controls. Additionally, analysis according to gender did not show any influence of sex on the association of IL23R with Fuchs’ syndrome. CONCLUSIONS: Our results suggested that the rs11209032 AA genotype of the IL23R gene may predispose for Fuchs’ syndrome in Chinese patients.